Explaining Customer Loyalty in AI Chatbot–Based E-Commerce Services: An Information Systems Success Perspective - Firgiawan Akbar; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2026)
The growing presence of AI chatbots across e-commerce platforms has prompted scholarly inquiry into how these systems build lasting customer loyalty beyond the point of initial adoption. This study aims to examine how chatbot-based services contribute to customer loyalty by drawing on the information systems success perspective. A quantitative approach was adopted, using Partial Least Squares Structural Equation Modeling (PLS-SEM) on data gathered from 132 Indonesian e-commerce users with prior experience interacting with AI chatbots. Results show that both information quality and system quality exert significant effects on use behavior and user satisfaction. Use and satisfaction were further confirmed as direct drivers of customer loyalty, framed here as net benefits, with use showing a comparatively stronger effect. These findings point to the conclusion that loyalty in AI chatbot-supported environments is cultivated primarily through repeated engagement and accumulated experience rather than being driven directly by system attributes. The study advances understanding of AI-enabled service outcomes by identifying the behavioral pathways through which chatbots produce long-term value. For practitioners, the findings suggest that e-commerce platforms seeking stronger loyalty should focus on functional reliability and create conditions that encourage sustained usage.